Sliding Wear Properties of Hybrid Aluminium Composite Reinforced by Particles of Palm Shell Activated Carbon and Slag - Yusoff, Zamri; Jamaludin, Shamsul Baharin; Amin, Misbahul; Ahmad Zaidi, Nur Hidayah (Journal of Science and Technology, 2010)
In present work, dry sliding wear tests were conducted on hybrid composite reinforced with natural carbon based particles such as palm shell activated carbon (PSAC) and slag. Hybrid composites containing 5 -20 wt.% of both reinforcements with average particles sizes about 125μm were prepared by conventional powder metallurgy technique, which involves the steps of mixing, compacting and sintering. Dry sliding experiments were conducted in air at room temperature using a pin-on-disc self-built attach to polisher machine. The disc which acted as the mating surface material was made of mild steel (120 HV) cut from commercial mild steel sheet (2 mm thickness) into 100mm diameter. The influence of the applied load was investigated under a constant sliding velocity of 0.1m/s with the applied loads at 3N, 11N and 51N. The contribution of the reinforcement content and the applied load as well as the sliding distance on the wear process and the wear rate have been investigated. The contribution of synergic factors such as applied load, sliding distance and reinforcement content (wt.%) have been studied using analysis of variance (ANOVA). All synergic factors contribute to the wear process of all tested composites. Among synergic factors, the applied load is the highest contribution to wear process on both composites (Al/PSAC and Al/Slag) and hybrid composite. The degree of improvement of wear resistance of hybrid composite is strongly dependent on the reinforcement content.